A review on the challenges affecting growth of Small & Medium Enterprises (SMES) in food manufacturer / Waliyyah Silong Taib & Nor Hidayah Mohamad Nasri - Silong Taib, Waliyyah; Mohamad Nasri, Nor Hidayah (2017)
Overall story of this study is to review on the challenges affecting growth of Small & Medium Enterprises (SMEs) in food manufacture. The intention of this study is to identify how the challenges can affect to SME’s failure and what the factors can raise the growth of SMEs in the industry. This study found out five challenges that affecting SME’s growth that may lead to the business failure. Therefore, we found that: lack of financing, increasing of operational cost, lack of knowledge, lack on human capital development, and food safety and hygiene are challenges of SMEs in food manufacturing. The theoretical framework was shown in this study to explain to the reader about our study as roughly. It is involve 3 variables which is Factor of Growth (DV), SMEs Failure (DV), and Challenges as independent variable. We found the finding based on the analyzing the table, graph, report survey, journal article, newspaper, annual report that reach from the available and trusted sources. The discussion and conclusion of this study has been argued in the last chapter of this study. Our discussions are answering back the research question and the objective.